The Pyrus bretschneideri invertase gene family: identification, phylogeny and expression patterns. Issue 1 (1st January 2020) - Wu, Tao; Liu, Zheng; Yang, Li; Cheng, Yinsheng; Tu, Junfan; Yang, Fuchen; Zhu, Hongyan; Li, Xianming; Dai, Yonghong; Nie, Xianshuang; Qin, Zhongqi
Abstract: Plant invertases comprise a family of enzymes that catalyze the irreversible hydrolysis of sucrose into glucose and fructose, which plays a crucial role in carbohydrate partitioning and regulating plant growth and development. However, currently, there is little information on the roles of invertases in the development of pear trees. In this study, we performed genome-wide identification of a total of 23 invertases from the predicted genome data of the pear plant ( Pyrus bretschneideri R.). Based on phylogenetic analysis, the pear invertases could be clustered into 13 acid invertase genes and 10 alkaline/neutral invertase genes. Chromosome location showed that tandem duplication and segmental duplication have played an important role in the expansion of acid and neutral/alkaline invertases in pear plants. Evolutionary analysis of invertases from pear and two model plant species ( Arabidopsis thaliana and Oryza sativa ) indicated that the evolutionary divergence of invertases occurred before the common ancestor of dicots and monocots. Tissue-specific expression analysis showed that the transcripts of all the identified invertase genes were detectable in various tissues. We hypothesize that the identified invertase genes all participate in regulating pear growth and development.